2017
DOI: 10.1093/ptj/pzx107
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality in Children With Cerebral Palsy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Then compared with other interventions, VR seems to be an effective intervention for improving motor function in children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(189 citation statements)
references
References 63 publications
12
144
0
10
Order By: Relevance
“…These findings are similar to those of Ravi & Kumar and Chen et al (13,14), who reported that MCVGs may be as effective as traditional occupational and physiotherapy methods. One study (42) reported higher compliance in the MCVG group compared with the control group, suggesting that MCVGs are a motivating training method; a finding also reported in other studies (7).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are similar to those of Ravi & Kumar and Chen et al (13,14), who reported that MCVGs may be as effective as traditional occupational and physiotherapy methods. One study (42) reported higher compliance in the MCVG group compared with the control group, suggesting that MCVGs are a motivating training method; a finding also reported in other studies (7).…”
Section: Discussionsupporting
confidence: 91%
“…One study (42) reported higher compliance in the MCVG group compared with the control group, suggesting that MCVGs are a motivating training method; a finding also reported in other studies (7). Chen and colleagues (14) found that engineer-built systems had a larger effect than MCVGs. However, such systems are not commercially available, are very large in size and are much more expensive than commercial MCVG, such as the Nintendo or Xbox platforms.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This space was set up in response to current evidence reporting the potential of VR for improving motor function and activity level in stroke and cerebral palsy [1,15]. Patients treated by our clinic include a variety of neurologic conditions, but primarily consists of cerebral palsy and traumatic brain injury.…”
Section: Kiosk Model For Pediatric Neurorehabilitation At Schön Clinimentioning
confidence: 99%
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%